(3fbd h ESJgdGc GdZGR GdWHjYi HeOjfI GdbGgQI (B: s (3HGSJNOGe fXe GdeYdheGJ GdLZQGajI (B/ s - (3jGSejf ESeGYjd eMehO GdSjO ESeGYjds; (3CMeO GdSjO GdRGedi (B: s; (3LeGd YHOGdQMje SQhQ (B: s ((3GdbGgQI (B: s (3jGSejf ESeGYjd eMehO GdSjO ESeGYjd (B: s, 2021)
(3jJfGhd gPG GdHMK fbd h ESJgdGc GdZGR GdWHjYi HeOjfI GdbGgQI HGSJNOGe fXe GdeYdheGJ GdLZQGajI h JfOQL gPg GdOQGSI Vef LZQGajG GdWGbI h GdJi JYO GMOi aQhY GdLZQGajG GdGbJUGOjI h GMOKgG fSHjG JQJHW WHjYI GdJbOe GdEbJUGOi JGQjNjG h LZQGajG h SQYJg HeOi JhajQ GdWGbI h GSJZdGdgG(B: (3h jYJeO Gdfeh GdGbJUGOi ai CMO GdCbGdje Ydi GSJZdGd eUGOQ GdWGbI GdcGefI HgG Ch fbdgG Gdjg(B: (3h dh JVGAdJ GSJKeGQGJ GdWGbI h CUHM EfJGLgG ZjQ eQf aEf GdbOQI GdEfJGLjI ai HYV GdbWGYGJ Sha JHbi YGWdI(B. (3CUHM GdZGR GdWHjYi jTcd CgejI fSHjI fXQG dchfg UOjbG ddHjFI(B: (3h dJbdjd GdGYJeGO Ydi GdeTJbGJ GdHJQhdjI LGAJ GdQSGdI ai CQHYI aUhd JSHbgG ebOeI h deMI JGQjNjI Yf h JdjgG NGJeI ceG jdi(B: (3GdaUd GdChd(B: (3CNJU HOQGSI GdYhGed GdLZQGajI GdeDKQI Ydi fbd h ESJgdGc GdZGR GdWHjYi HeOjfI GdbGgQI(B: (3aCfbSeJ GdYhGed Gdi WHjYjI h HTQjI h JeKdJ GdWHjYjI ai GdJQcjH GdLjhdhLi(B: (3h eXGgQ GdSWM(B: (3h GdYhGed GdHjFjI(B: (3CeG GdYfUQ GdHTQi acGf ddScGf h GdYeQGf CKQ Ydi GdGSJgdGc h LGAi GdSjGSGJ GdMchejI Vef GdYfGUQ GdHTQjI(B. (3Ke OQGSI JhRjY THcI GdZGR GdWHjYi h NUGFUgG HefWbI GdOQGSI HGdaUd GdKGfi h GdPi fGbT JWhQ CfJGL GdZGR(B: (3ceG JfGhd GdTHcI ef MjK GdJchjf(B: (3h GdNUGFU(B. (3NUU GdaUd GdKGdK dOQGSI ESJgdGc GdZGR GdWHjYi HeOjfI GdbGgQI(B: (3aJfGhd GdJWhQ GdJGQjNi dCSJgdGc GdZGR(B: (3h JWhQ GdGfeGW(B: (3h GdGSJgdGc Ydi eSJhi GdbWGYGJ GdeNJdaI(B. (3Ke LGA GdaUd GdQGHY defGbTI eTcdGJ GdZGR HefWbI GdOQGSI h GdMdhd GdebJQMI(B: (3YQV Cge GdeTcdGJ h GdJi GfbSeJ deTcdGJ eQJHWI HEeOGO GdZGR(B: (3eTcdGJ GbJUGOjI(B: (3eTcdGJ eNJdaIs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdBOGH (B- (3bSe GdLZQGajGs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdWGbI GdeJLOOIs; (3GdbGgQIs; (3GdHjFIs; (3GdWGbIs; (3GdZGR GdWHjYis